Answer:
C
Step-by-step explanation:
We know every triangle equals 180 so were just going to take 180 - 42 = 138 then were going to do 138 - 67 = 71 we can check our work by doing
42 + 67+ 71 = 180. We also know 67 + 42 = 109.
Lets look at our answers;
A. 109 = 180 + x When solved it gave me; x = -71. We got a positive 71 so this is incorrect.
B. x + 42 = 67 When solved it gave me; x = 25, which is incorrect.
C. x = 180 - 109 When solved it gave me; x = 71
D. 42 + 67 - x = 180 When solved it gave me; x = - 71
Therefore the answer is C.
Is there a equation? Or do you just wanna know what the sum of two binomials equal?
Answer:
-21/4x-1/2
Step-by-step explanation:
-1/2(-3/2x+6x+1)-3x
3/4x-3x-1/2-3x
3/4x-3x-3x-1/2
3/4x-6x-1/2
3/4x-24/4x-1/2
-21/4x-1/2
Answer:
f(x) = (8/3)x(x - 1).
Step-by-step explanation:
The vertex form of the function is
y = a(x - 1/2)^2 - 2/3 where a is some constant.
Now the roots are 0 and 1 so
For x = 0
0 = a(-1/2)^2 - 2/3
1/4 a = 2/3
a = 2/3 / 1/4 = 8/3.
So the function is
f(x) = (8/3)(x - 1/2)^2 - 2/3.
3 f(x) = 8(x - 1/2)^2 - 2
= 8(x^2 - x + 1/4) - 2
= 8x^2 - 8x + 2 - 2
3 f(x) = 8x(x - 1)
f(x) = (8/3)x(x - 1).